Determinants of Students’ Learning Motivation - Cantik Wasitaningsih; Elva Nuraina; Nur Wahyuning Sulistyowati (Jurnal Manajemen Pendidikan, 2025)
Background Differences in parental approaches to educating children, the diversity of peer characteristics, the adequacy of learning facilities, and the still relatively low level of students’ self-control can influence students’ learning motivation. Strong learning motivation among students contributes significantly to the achievement of high-quality education. Purpose This study aims to examine the partial effects of parental roles, peer influence, learning facilities, and self-control on students’ learning motivation. Design/method/approach This study employs a descriptive quantitative research design using a questionnaire to collect data from students enrolled in the Elementary School Teacher Education, Guidance and Counseling, Accounting Education, Economics Education, Accounting, Informatics Engineering, and Sport Science programs at Universitas PGRI Madiun. The population consisted of 500 students, from which 222 respondents were selected through random sampling. Data analysis was conducted using SmartPLS. Results The study found that students’ learning motivation is partially influenced by parental roles, peer influence, learning facilities, and self-control. Contribution/value This study contributes to the development of knowledge in the field of education by examining the influence of parental roles, peer influence, learning facilities, and self-control on students’ learning motivation. In addition, the findings provide valuable information for the academic community of Universitas PGRI Madiun in supporting the management and evaluation of study programs, faculties, and the university as a whole.